The Impact of Live Streaming on Social-Media on The Quality of TVRI South Sulawesi's Program - Sitti Wahyuni Artini (International Journal of Science and Society, 2022)
TVRI South Sulawesi is transforming the media by helping to expand the reach and improve the quality of broadcast programs by utilizing social media platforms. With the live streaming feature on several social media platforms, TVRI South Sulawesi uses this feature to broadcast its broadcasts through social media platforms to make it easier for the public to reach TVRI South Sulawesi broadcasts and get feedback regarding broadcast programs. This study was conducted to examine the impact of social media live streaming on the content quality of TVRI Sulawesi Selatan’s programs. In order to gather information for this study’s qualitative methodology, observation, and interviews were used. The study involved five informants who were leaders and employees of South Sulawesi TVRI and the community. The theory of media convergence is used by researchers to help understand the presence of new media on social interaction and integration with old media. The results of this study suggest that TVRI South Sulawesi utilizes the live streaming feature on three platforms, namely Youtube, Instagram, and Facebook. The transformation that has been carried out is proven by the expansion of broadcast coverage that can improve the quality of TVRI South Sulawesi's broadcast programs, namely creating new broadcast programs following the audience's interest, updating old programs, and improving the quality of TVRI South Sulawesi news. This research can contribute to further research on how media transformation can affect the development of the television industry in Indonesia by enriching broadcast content and expanding audience reach.